Adult attachment and self concept - Binti Mohammad Zamzur, Amie Nursyuhadah; Yahya, Fatahyah (Universitas Negeri Padang, 2019)
This study aims to identify the relationship between adult attachment and self-concept among year one and year two counselling students in University Malaysia Sarawak (UNIMAS). This research is correlational research design. The sample consisted of 52 respondents. The study involves two main variables of Adult Attachment and Self-Concept. In this study, the questionnaires used are Experience in Close Relationship (ECR) and Robson’s Self-Concept Questionnaire (SCQ). Statistical Package for the Social Sciences (SPSS) analysis showed a negative significant relationship between Attachment Anxiety and Self-Concept with Pearson correlation value (p = 0.005, r = -0.383).This finding might be due to the respondents’ backgrounds which are Counselling students. It is suggested that the trainee counsellors to gain awareness on the importance of having positive self-concept in order to be competence and professional counsellor.